Increasing Of Geometry Learning Outcomes Using Savi Method With Fifth Grade - Widyawati, Defrina Martha; Relmasira, Stefanus C.; Juneau, Janelle L. (Universitas Pendidikan Ganesha, 2018)
The purposes of this research are to know if the implementation of SAVI method is able to increase the mathematics learning outcomes at SD Negeri Gedangan 01 Tuntang and describing the implementation of SAVI Method. This research type is collaboration classroom action research. The subject of this research is the fifth grade of SD Negeri Gedangan 01 Tuntang consists of 21 students. The research instruments used to collect the data are observation sheets and evaluation test that analyzed by quantitatively. The result shows academic achievement increase to 33% from the pre-cycle to cycle one. In cycle two, the score was significantly increased to 48%. The reason why researcher used the SAVI method is because it focuses on the all sense of students that used in the learning process. Researcher used video interactive, some picture, some activities such as arranged the puzzle and tangram; make the solid geometry from the wood lighter and this activity made students to use their all sense. The condition of the teaching and learning process had been conducive and enthusiast from the all students in grades five. Students have many types of learning style like visual, audio, kinesthetic, and tactile. Thus, when SAVI was implemented students got the chance to learn well in the teaching and learning process